PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 008 BUKIT KAYU KAPUR - Yasi Sartika Dewi Sartika; Gustimal Witri Witri; Hendri Marhadi Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: A problem in this Research is lowering nya of result of learning Mathematics of student of class of III SD Country 008 wood Hill Calcify with the mean assess the score of early 65,4. This research aim to to increase result of learning mathematics of student of class of III SD Country 008 Wood Hill Calcify the melalul " Applying Model The Study [of] Pursuant To Problem ( PBM )". Instrumens of data collecting of at this skripsi is  [of] result of learning student, sheet of activity perception learn and sheet of perception of aktitas student. This research [is] executed [at] April month;moon 2014 executed [by] as much this 2 siklus.Subyek research [is] student of class of III SD Country 008 Hill of Chalk Wood amounting to 25 student people. Activity learn the first cycle I meeting with the percentage 55 % with the category less , mounting [at] second cycle I meeting with the percentage 70 % categorize enough, later;then experience of the improvement [of] [at] first cycle II meeting with the good category, and [at] second cycle II meeting with the percentage 90 % categorize very good. While result of perception of student activity [of] [at] first cycle Ipertemuan 45 % category less once, second meeting 60 % enough , [at] first cycle II meeting 80 % with the good category and pertemuankedua 85 % with the good category. Seen from activity result learn and student from cycle I to cycle II experience of the improvement. To result of learning visible [of] pengingkatannya from daily restating of cycle of I and cycle II. [At] daily restating result of cycle I in each cycle also experience of the daily peningkatan,pada restating of cycle of I mean 72, 4 or experience of the improvement 12 %, at daily restating of cycle of II mean 79, 2atau experiencing of improvement 26 %. From this research [is] inferential that applying model the Study of Pursuant to Problem ( PBM ) can improve the result learn the mathematics of student of class of III c SD Country 008 Wood Hill Calcify. Keyword : Study [of] Pursuant To Problem ( PBM ) Result Learn mathematics